Pendidikan Karakter Berbasis Moderasi Beragama untuk Meningkatkan Toleransi Siswa (Studi Kasus pada MTs Nurul Jadid Buleleng Bali) - Rofiqi (Khatulistiwa Insight: Islamic Education and Learning, 2025)
This study analyzes the implementation of character education based on religious moderation at MTs Nurul Jadid Buleleng, Bali, and its impact on students' tolerance attitudes. Using a qualitative approach with a case study method, data were collected through observations, in-depth interviews, and documentation. The findings indicate that religious moderation is implemented through curriculum integration, extracurricular activities, and daily habituation. Its impact is reflected in increased tolerance, reduced cases of intolerance, and active student participation in interfaith social activities. However, several challenges persist, such as the influence of social media, limited parental involvement, and a lack of teacher training. Therefore, this study recommends strengthening the curriculum, providing teacher training, enhancing digital literacy, and fostering collaboration with the community to reinforce character education based on religious moderation in schools.